2013
DOI: 10.1002/rcs.1527
|View full text |Cite
|
Sign up to set email alerts
|

Impact of navigated‐control assistance on performance, workload and situation awareness of experienced surgeons performing a simulated mastoidectomy

Abstract: The results demonstrate the potential of NC support in terms of lower workload and enhanced patient safety. Cost effects might be reduced by remodelling the control function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…37 In addition, interruptions in the surgeon's workflow caused by the technological implementation have been addressed. 29 The learning curve in robotic surgery varies, depending on the complexity of the procedures and on the surgeon's experience of similar technology and familiarity with the procedure in question. 22 In recent work, it was suggested that the minimal training before patient-related console time should involve live and video observations and should confer knowledge, table assistance and basic skills.…”
Section: Human-robot Interaction In Robotic Surgerymentioning
confidence: 99%
See 4 more Smart Citations
“…37 In addition, interruptions in the surgeon's workflow caused by the technological implementation have been addressed. 29 The learning curve in robotic surgery varies, depending on the complexity of the procedures and on the surgeon's experience of similar technology and familiarity with the procedure in question. 22 In recent work, it was suggested that the minimal training before patient-related console time should involve live and video observations and should confer knowledge, table assistance and basic skills.…”
Section: Human-robot Interaction In Robotic Surgerymentioning
confidence: 99%
“…Leaving virtual landmarks on the image (#19 in Table 2) could serve several functions. In addition to helping surgeons orient and navigate (cf image-guided navigation 29,37 ), the surgeons saw potential in marking areas where extra caution is needed (cf 'no-go' zones 5,9,11,12,18,34 ; #11 in Table 2). The use of markers in a 3D environment for realigning the robotic instruments has already been suggested.…”
Section: Haptic Feedback (#7 and #8) And Head-mounted Displays (#4 mentioning
confidence: 99%
See 3 more Smart Citations